Sosialisasi Tanggap Darurat Pencegahan Covid-19 di Kepulauan Talaud - I Made Artika; Mutmainnah A. Umar (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Since the World Health Organization or WHO declared that the Coronavirus disease (Covid-19) is a pandemic, the President of the Republic of Indonesia and the Regional Government and their staff have worked hand in hand to make some tactical steps to prevent the spread of this virus. The public must be informed on the dangers of Covid-19, through creation of special protocols which are expected to prevent the spread of this virus. The purpose of this activity was to conduct socialization directly or indirectly in providing education, convincing, and providing an overview of the dangers of the Covid-19 Virus and applying health protocols to the community in Melonguane District, Talaud Islands Regency, North Sulawesi Province. This activity took place from July 7 to August 28, 2020. The results of this activity showed that the people in the Talaud Islands have understood the importance of using good and correct masks when outside the home and also the use of hand soap or hand sanitizer which can help people to avoid this dangerous virus. Keywords: covid-19, emergency response, Kepulauan Talaud, Melonguane